Promising breeding material of green pea - I.M. Kaygorodova; O.N. Pyshnaya; E.P. Pronina (Овощи России)
The green pea collection consisting of 277 geographically distant samples varied in quantitative and qualitative traits was estimated. The molecular analysis of selected samples was conducted for the purpose of reciprocal crossing.